Herba Cistanche (Rou Cong-Rong): One of the Best Pharmaceutical Gifts of Traditional Chinese Medicine - Li, Zhiming; Lin, Huinuan; Gu, Long; Gao, Jingwen; Tzeng, Chi-Meng (Frontiers in Pharmacology, 2016)
Cistanche species, known as Rou Cong-Rong in Chinese, are an endangered wild species and are mainly distributed in the arid lands and warm deserts of northwestern China. Within Traditional Chinese Medicine (TCM), Herba Cistanche is applied as a tonic and/or in a formula for chronic renal disease, impotence, female infertility, morbid leucorrhea, profuse metrorrhagia and senile constipation. The chemical constituents of Herba Cistanche mainly consist of volatile oils, non-volatile phenylethanoid glycosides (PhGs), iridoids, lignans, alditols, oligosaccharides and polysaccharides. There have been an increasing number of studies focusing on its bio-activities, including antioxidation, neuroprotection, and antiaging. The objective of this review is to introduce this herb to the world. Its taxonomy, distribution, and corresponding biological functions and molecular mechanisms are addressed in this review.